Surgical management of intraoperatively diagnosed portal annular pancreas: Two case reports. Issue 50 (17th December 2021) - Abe, Nobutaka; Lee, Sang-Woong; Shimizu, Tetsunosuke; Asakuma, Mitsuhiro; Taniguchi, Kohei; Tomioka, Atsushi; Hirokawa, Fumitoshi; Uchiyama, Kazuhisa
Abstract: Rationale: Portal annular pancreas (PAP) is a rare pancreatic anomaly characterized by portal vein encasement in the pancreatic parenchyma. Due to its rarity, PAP may often be missed on preoperative computed tomography (CT) review, and surgeons may face challenges in dealing with an unexpected intraoperative encounter with PAP. We documented 2 such intraoperatively diagnosed cases and illustrated their surgical management. Patients' concerns: In case 1, a 70-year-old man was found to have a 15-mm mass in the pancreatic body and dilatation of the peripheral main pancreatic duct on enhanced CT. Case 2 involved a 46-year-old woman with a history of familial adenomatous polyposis, and rectal cancer with a mass in the duodenal papilla. Diagnoses: The patient in case 1 was diagnosed with resectable pancreatic cancer. In case 2, the patient was diagnosed with duodenal papillary carcinoma. Interventions: In case 1, the patient underwent distal pancreatectomy with lymph node dissection. In case 2, the patient underwent pancreaticoduodenectomy. Intraoperatively, PAP was observed in both cases. In case 1, after the usual transection at the right border of the portal vein, an additional dissection was performed on the dorsal pancreas using a powered linear stapler. In case 2, an additional section was made in the pancreatic body caudal to the cricoid pancreatic junction so that the pancreatic cross-section was oriented in 1 plane. Outcomes: The patient in case 1 was discharged without complications. In case 2, although the patient had a grade-B pancreatic fistula (International Study Group of Pancreatic Fistula Classification), the patient recovered conservatively and was discharged without significant complications. In both cases, a retrospective review identified PAP in patients' preoperative CT images. Lessons: Both cases required ingenuity during pancreatectomy. Awareness about PAP and its management will enable surgeons to prepare for unexpected encounters with the condition. Moreover, surgeons (especially pancreatic surgeons) should consider the possibility of PAP while managing pancreatic anomalies to make appropriate treatment decisions.